LISINOPRIL USAGE IN CARDIOLOGIC PRACTICE: DATA OF EVIDENCE BASED MEDICINE - N. P. Kutishenko; S. J. Martsevich (Рациональная фармакотерапия в кардиологии, 2015)
Data of multicenter clinical trials on assessment of angiotensin converting enzyme inhibitor, lisinopril efficacy in therapy of patients with arterial hypertension, heart failure, myocardial infarction complicated with left ventricle dysfunction and diabetes (GISSI-3, ATLAS, ALLHAT, EUCLID) are presented in the review. The results of these trials establish more active usage of lisinopril in clinical practice.